A glycopeptide dendrimer inhibitor of the galactose specific lectin LecA & of Pseudomonas aeruginosa biofilms - Kadam, Rameshwar U.; Bergmann, Myriam; Hurley, Matthew; Garg, Divita; Cacciarini, Martina; Swiderska, Magdalena A.; Nativi, Cristina; Sattler, Michael; Smyth, Alan R.; Williams, Paul; Cámara, Miguel; Stocker, Achim; et al. (Wiley-VCH Verlag, 2011)
Biofilm inhibition is achieved with a phenylgalactosyl peptide dendrimer (see picture) that binds to the galactose-specific lectin LecA of P. aeruginosa. The multivalency of the ligands is critical for biofilm inhibition, although the nature of the linker between the peptide dendrimer and the galactose can provide additional contacts to the lectin and also has an effect on the interaction.